NiS2 nanosheet array: A high-active bifunctional electrocatalyst for hydrazine oxidation and water reduction toward energy-efficient hydrogen production. (March 2017) - Wang, Jianmei; Ma, Xiao; Liu, Tingting; Liu, Danni; Hao, Shuai; Du, Gu; Kong, Rongmei; Asiri, Abdullah M.; Sun, Xuping
Abstract: The sluggish kinetics of water oxidation has severely hindered the energetic convenience of electrochemical water splitting. In this work, we describe our recent finding that NiS2 nanosheet array on Ti mesh (NiS2 /TiM) is a superior catalyst for hydrazine oxidation reaction (HzOR) with the demand of potential of 218 mV to drive 300 mA cm −2 in 1.0 M KOH with 0.5 M hydrazine. Interestingly, its high activity toward hydrogen evolution reaction enables it as a bifunctional catalyst for energy-efficient electrolytic hydrogen generation, and the two-electrode alkaline electrolyzer using NiS2 /TiM as both anode for HzOR and cathode for HER needs a cell voltage of only 0.59 V to attain 50 mA cm −2, 1.34 V less compared with pure water splitting to achieve the same current density, promising the use of such 3D catalyst electrode toward energy-saving electrochemical production of hydrogen fuels.